2020
DOI: 10.1364/ao.384614
|View full text |Cite
|
Sign up to set email alerts
|

Measurement method of optical properties of ex vivo biological tissues of rats in the near-infrared range

Abstract: An optical fiber-based supercontinuum setup and a custom-made spectrophotometer that can measure spectra from 1100 to 2300 nm, are used to describe attenuation properties from different ex vivo rat tissues. Our method is able to differentiate between scattering and absorption coefficients in biological tissues. Theoretical assumptions combined with experimental measurements demonstrate that, in this infrared range, tissue attenuation and absorption can be accurately measured, and scattering can be described as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The results were images at various depths based on reflectivity in the NIR region. A prominent absorber in the NIR region is water with absorption bands at 1450 nm and 1900 nm [78]. Weak NIR absorption bands within tissue originate from biomolecules such as lipids, collagen, and proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were images at various depths based on reflectivity in the NIR region. A prominent absorber in the NIR region is water with absorption bands at 1450 nm and 1900 nm [78]. Weak NIR absorption bands within tissue originate from biomolecules such as lipids, collagen, and proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the biomolecules, poor light absorption in the NIR spectral range a sample thickness of 16 µm was not sufficient to detect moleculespecific information in the NIR range. Additionally, absorption bands of these biomolecules are usually overlapped by the strong absorption properties of water [78]. A statement regarding the air-dried tissue's water content based on other modalities of the imaging system is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Its potential in radiation attenuation applications warrants a comprehensive study to assess its attenuation properties and suitability for practical use (Chang et al, 2021). Through this investigation, we seek to contribute to the knowledge base on the attenuation properties of Ozanogogo Kaolin and provide valuable data for applications in radiation shielding, material characterization, and non-destructive testing (Sánchez-Cano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…11 Bickel et al 12 demonstrated that polarization in light scattering could be used as an effective tool in biological study. Various biological tissues, including tissues from cardiac muscle, brain, liver, kidney cortex, loin muscle, and tendon of pigs, [13][14][15][16] tissues from heart, brain, retina, kidney, and spleen of rats, 17 cardiac tissues of Lewis rats, 18,19 human breast cancer tissues, [20][21][22] and invasive breast cancer specimens, [23][24][25] have been characterized using a wide variety of optical modalities such as polarimetric light microscopy (PLM), [23][24][25] linear polarization spectroscopy, [23][24][25] Mueller polarimetry, 26 near-infrared spectroscopy (NIRS), [20][21][22]27 and optical coherence tomography (OCT). 13,14 Sprenger et al 23 devised a quantitative approach for assessing the tumor's stroma ratio by combining PLM and linear polarization in breast cancer specimens.…”
Section: Introductionmentioning
confidence: 99%
“…This method produced high contrast images of stromal morphology in breast tumor specimens. 25 Sanchez-Cano et al 17 developed an optical fiber-based supercontinuum setup consisting of a spectrophotometer capable of measuring spectra ranging from 1100 to 2300 nm for characterizing the absorption, attenuation, and scattering spectral coefficients of ex vivo rat tissues of heart, kidney, brain, retina, and spleen. For detecting glucose in ex vivo human gingival tissues, John et al 28 used a wideband supercontinuum laser source filtered by bandpass filters with multiple wavelengths of 1300, 1580, and 2100 nm based on low coherence interferometry.…”
Section: Introductionmentioning
confidence: 99%